Existence and uniqueness of solution of mixed stochastic differential equation driven by fractional Brownian motion and wiener process - Mishura, Y.; Posashkov, S. (Інститут математики НАН України, 2007)
The existence and uniqueness of solution of stochastic differential equation driven by standard Brownian motion and fractional Brownian motion with Hurst parameter H belongs (3/4, 1) is established.